2004
DOI: 10.1111/j.1559-1816.2004.tb02688.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection Interviews of Overweight Job Applicants: Can Structure Reduce the Bias?1

Abstract: The purpose of these studies was to extend the benefits of the structured selection interview beyond its psychometric advantages, and to include its potential to mitigate biases against overweight applicants. In the first study, 133 participants witnessed a videotaped interview and were asked to rate the performance of the candidate. Videotapes varied by structured/unstructued interview scripts and average weighdoveweight job applicant. Results confirmed the discrimination bias against overweight interviewees,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 77 publications
(68 reference statements)
3
35
0
Order By: Relevance
“…However, this finding is consistent with those of Kutcher and Bragger (2004) and Bragger et al (2002) who used a similar methodology to investigate weight bias and pregnancy bias, respectively, in the structured and unstructured job interview. These results are likely a function of the narrow range of starting salaries listed in the job description and the inexperience and inability of undergraduate students to make realistic judgments about salary recommendations.…”
Section: Findings and Implicationssupporting
confidence: 92%
See 2 more Smart Citations
“…However, this finding is consistent with those of Kutcher and Bragger (2004) and Bragger et al (2002) who used a similar methodology to investigate weight bias and pregnancy bias, respectively, in the structured and unstructured job interview. These results are likely a function of the narrow range of starting salaries listed in the job description and the inexperience and inability of undergraduate students to make realistic judgments about salary recommendations.…”
Section: Findings and Implicationssupporting
confidence: 92%
“…Results supported that interview structure did indeed reduce the leniency bias toward candidates with disabilities. These findings, when considered with those of other studies (e.g., Bragger et al, 2002;Kutcher & Bragger, 2004), indicate that efforts to structure an organization's interview can effectively improve not only the accuracy, but also its fairness and defense against common biases and stereotypes.…”
Section: Findings and Implicationssupporting
confidence: 57%
See 1 more Smart Citation
“…Additionally, the lack of impact on affect could have been due in part to the structured interview format used for this study. Kutcher and Bragger (2004) found that a highly structured interview reduced bias against obese applicants, Note. 0 = Caucasian and 1 = African American.…”
Section: Discussionmentioning
confidence: 98%
“…What can we do to reduce bias? We've mentioned that a recent laboratory study found that increasing the structure of job interviews can decrease obesity bias (Kutcher & Bragger, 2004). Future work should continue to turn toward creating interventions to try to reduce or, ideally, eliminate the impact of obesity-based prejudice at work.…”
Section: T a B L E I V Anova Main Effects For Race Of Rater On All Dementioning
confidence: 93%